Variability of Water Vapor Using Ground and Satellite Measurements Over Indo-Gangetic Basin and Analysis of Its Relation with Temperature & Rainfall: Understanding the variability of water vapor and its impacts on climate, human health, and environment in the Indo-Gangetic Basin (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The Climatic and Environmental effects of atmospheric water vapor are critical issues in global science community because water vapor is known to affect rainfall, temperature, greenhouse effect, human health and radiation budget. The Indian subcontinent is one of the highest populated, industrialized and developing regions where water vapor content is responsible for rainfall, affects the climate and environment, but also human health and the society. In the present study, variability of total water vapor columns of atmosphere has been studied over three locations (Jaipur, Kanpur and Gandhi College) located in Indo-Gangetic Basin during 2014-2017 using ground based (AERONET) as well as satellite measurements (MODIS on board of TERRA, TRMM, AIRS). The ground data has also been compared with satellite data. The results are found to be highly correlated with some fluctuations observed. The IGB is of great interest due to its unique topography and having more population.